Congenital Adrenal Hyperplasia (CAH) and Gitelman Syndrome (GS): Overlapping Symptoms in an Uncommon Association - Valeria Calcaterra; Giulia Roberto; Anna La Rocca; Beatrice Andrenacci; Federico Rossi; Gian Vincenzo Zuccotti; Valentina Fabiano (Hindawi Limited, 2021)
Background. Classical salt-wasting (SW) congenital adrenal hyperplasia (CAH) and Gitelman syndrome (GS) are two genetic conditions in which dyselectrolytemia may occur. No association between the two conditions has been previously described. Case Presentation. We present the case of a boy with a neonatal diagnosis of SW-CAH who showed low potassium blood levels from the age of 15 years. This electrolytic alteration was, at first, attributed to an excessive action of mineralocorticoid drugs. Due to persistence of hypokalemia, SLC12A3 whole genome sequencing was performed, showing a heterozygous C to T base pair substitution at position 965 in gene SLC12A3. This mutation is related to Gitelman syndrome with autosomal recessive transmission. Conclusions. SW-CAH and GS determine opposite values of potassium in the absence of specific therapy, with a natural tendency to compensate each other. The symptom overlap makes diagnosis difficult. Organic causes of hypokalemia in patients undergoing life-saving therapy should not be excluded.